2005
DOI: 10.1111/j.1533-2500.2005.05314.x
|View full text |Cite
|
Sign up to set email alerts
|

Sphenopalatine Ganglion Pulsed Radiofrequency Treatment in 30 Patients Suffering from Chronic Face and Head Pain

Abstract: This study evaluated the efficacy of sphenopalatine ganglion pulsed radiofrequency (SPG-PRF) treatment in patients suffering from chronic head and face pain. Thirty patients were observed from 4 to 52 months after PRF treatment. The primary efficacy measures were the reduction in oral medication use, including opioids, time-to-next-treatment modality for presenting symptoms, duration of pain relief, and the presence of residual symptoms. Secondary objectives included the evaluation of adverse effects and compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 15 publications
(15 reference statements)
2
51
0
1
Order By: Relevance
“…However, unexpected adverse effects were reported only in a few cases during RFTC of the SPG for headache. 11,12 The principle of radiofrequency (RF) is that it is in the form of alternating electrical current and the heat is generated around the tip of the electrode. Cell culture studies have shown that exposure creates a biological effect due to the induction of early gene expression in the dorsal horn.…”
Section: Discussionmentioning
confidence: 99%
“…However, unexpected adverse effects were reported only in a few cases during RFTC of the SPG for headache. 11,12 The principle of radiofrequency (RF) is that it is in the form of alternating electrical current and the heat is generated around the tip of the electrode. Cell culture studies have shown that exposure creates a biological effect due to the induction of early gene expression in the dorsal horn.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the needle can generate an adequate thermocoagulation in the ganglion. Right stimulation response can justify subsequent thermocoagulation of the SPG leading to adequate pain relief (5)(6)(7)(8)(9)(10).…”
Section: Discussionmentioning
confidence: 99%
“…Pulsed radiofrequency would seem to be safer; however, there are only few case reports of its application in conjunction with SPG [10,11].…”
Section: Complications Of Radiofrequency Ablationmentioning
confidence: 99%